Lithium Induced Histological Alteration in Testes of Albino Rats and Their Amelioration with Vitamin E (Medical Forum Monthly, 2024)
Objective: To evaluate the lithium induced histological alteration in testes of albino rats and their amelioration by Vitamin E.Study Design: Experimental studyPlace and Duration of Study: This study was conducted at department of Anatomy, Baqai Medical University, Karachi from July 2010 to August 2010.Materials and Methods: The rats were assigned into three experimental groups (eight rats/group): control group, lithium group and lithium plus vitamin E treated group. Lithium (50 mg/kg/day) and vitamin E (50mg/kg/day) were given intraperitoneally for 21 days. At the end of experiment, rats were sacrificed and testes removed and processed for routine H&E. Slides were studied for histological examination under light microscope.Results: Lithium treated rats showed decreased body and testicular weights, spermatogenic cells such as primary and secondary spermatocytes and spermatids were decreased, very little spermatozoa were seen in lumen of seminiferous tubules, significant increase in tubular count observed while tubular diameter, germinal epithelial thickness, number and size of nuclei of leydig cells were highly significantly reduced. In lithium plus vitamin E treated group, body and testicular weight, primary and secondary spermatocytes, spermatids were restored near to control. Tubular lumen also showed many spermatozoa. Tubular diameter, germinal epithelial thickness, number and size of nuclei of leydig cells were also returned to controlConclusion: Our study conclude that lithium causes detrimental effect on testicular morphology through oxidative stress and vitamin E provided protection through its antioxidative property.